Turn-by-turn data analysis for PETRA III - Kling, A; Balewski, K; Bartolini, R (2010)
PETRA III is a 3rd generation synchrotron radiation light source which started commissioning in April 2009. Turn-by-turn capabilities are available for all 227 BPMs installed in the storage ring thus providing a powerful diagnostic tool for the characterization of the linear and nonlinear motion of the stored beam. We report on first results of beam dynamics studies using multiturn data acquired at PETRA III and first steps towards a calibration of the linear and nonlinear lattice model of the storage ring.